Edukasi Gizi dan Pelatihan Puding Pakcoy sebagai Upaya Pencegahan Stunting di Nagarasari - Tria Ramadani; Priscilla Windy Aurelia; Nanda Agustina; Indah Mulyani; Regina Rostarina Julyanti; Brigita Fauziastuti Sasmita; Nazzal Nurhakim; Indri Ayu Widiyanti (FKIP Universitas Mataram, 2026)
Stunting remains a nutritional problem that requires serious attention because it can affect children’s growth and development in the long term. One way to prevent stunting is through nutrition education and the promotion of nutritious local foods to the community. This community service activity aimed to improve the knowledge and skills of mother volunteers and the surrounding community in preventing stunting through nutrition education and a local food innovation in the form of pakcoy pudding, “PuCoy.” The activity was held on April 19, 2026, at the Balai Riung Kampung KB Bantarsari in Tasikmalaya City, involving 25 participants. The method used was participatory education based on community empowerment through the delivery of materials, demonstrations, discussions, and evaluations. The results of the activity showed an increase in participants’ understanding of balanced nutrition and the importance of preventing stunting. In addition, participants acquired the skills to process local foods into healthy and nutritious snacks. The PuCoy innovation received a positive response from participants because it is easy to make, nutritionally valuable, and has the potential to serve as an alternative to supplementary feeding (PMT) at Posyandu clinics. This activity demonstrates that participatory education is effective in raising community awareness and skills regarding the use of local foods for stunting prevention.